Study of Development Staff at the District and Lower Levels - Planning Commission (Planning Commission, 1968)
At the instance of Planning Commission, Programme Evaluation Organisation took up a study of the pattern of development staff at the district and lower levels in order to ascertain the strength of different categories of personnel located at various operational levels in the district.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission